KONSEP PENDIDIKAN PRANATAL DAN POSTNATAL DALAM KELUARGA - Putri Sinta Nuriah Yusuf; Arin Khairunnisa (Nusantara Hasana Journal, 2023)
This study aims to determine the concept of prenatal and postnatal education in the family. Education is a process of learning knowledge, skills and habits of a group of people which are passed down from one generation to the next through teaching, training and research. If related to the notion of education as described above, the education of children in the womb is a conscious effort of parents (husband -wife) to educate their children who are still in the womb of the wife. A conscious effort here is specifically aimed at and carried by both parents because it is not possible to educate a child in the womb (prenatal), let alone taught except by the parents themselves. Postnatal education is human education in the family environment starting from birth to the end of his life. All kinds of life sciences obtained from the family are the result of the postnatal family education process. From birth humans have been taught how to lie on their stomach, drink, eat, walk to religious knowledge. Just like prenatal education whose goal is to ensure that humans are born into the world, Dr. Dety Mulyati stated that postnatal education is shown as a guarantee so that humans are good and do not experience significant difficulties during the process of human life. The method used is the literature review method. It turns out that prenatal and postnatal education is very important for the education of the child both in the womb and at the time of delivery for the rest of his life.